1988
DOI: 10.1021/np50059a016
|View full text |Cite
|
Sign up to set email alerts
|

Two New Dihydrochalcones from Lindera erythrocarpa

Abstract: Two new dihydrochalcones, dihydropashanone [1] and dihydrokanakugiol [2], were isolated from Lindera erythrocarpa. Their structures were elucidated by chemical and spectroscopic means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 6 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…The separation in the IP values for the different structures is also smaller in solution than in vacuo, indicating that, in solution, most compounds have nearly similar tendency to react through ET mechanism. The ET mechanism may offer an explanation for the observation that LD, LR and mLR have the ability to scavenge free radical species, as reported by some experimental researchers [2][3][4][5][6][7][8][9][10]. In all the media, the tendency to scavenge free radicals increases with the increase in the number of OCH 3 groups as substituents on the main moiety, in this way, mLR and LD have the highest and the lowest tendency, respectively, to scavenge free radical species.…”
Section: H-bond Parameters a Bcp Parametersmentioning
confidence: 72%
See 2 more Smart Citations
“…The separation in the IP values for the different structures is also smaller in solution than in vacuo, indicating that, in solution, most compounds have nearly similar tendency to react through ET mechanism. The ET mechanism may offer an explanation for the observation that LD, LR and mLR have the ability to scavenge free radical species, as reported by some experimental researchers [2][3][4][5][6][7][8][9][10]. In all the media, the tendency to scavenge free radicals increases with the increase in the number of OCH 3 groups as substituents on the main moiety, in this way, mLR and LD have the highest and the lowest tendency, respectively, to scavenge free radical species.…”
Section: H-bond Parameters a Bcp Parametersmentioning
confidence: 72%
“…Lucidone (LD), linderone (LR) and methyllinderone (mLR) are acylcyclopentene-1,3-dione derivatives isolated from Lindera erythrocarpa Makino plant, which belongs to the large Lauraceae family and consists mostly of trees or shrubs [1][2][3][4][5][6]. In most part of the world where this plant is found, it is utilised as a traditional medicine for the treatment of several illnesses including analgesic, digestive, diuretic and headache problems [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lindera erythrocarpa Makino is one of the Lauraceae woody plants, which are distributed widely in Asia, including Taiwan, Japan, Korea and China. The fruit of L. erythrocarpa is used as a folk medicine as for its analgesic, digestive, diuretic, antidote and antibacterial properties (Liu et al, 1973;Ichino et al, 1988). However, little scientific study has been reported on the bioactivities of L. erythrocarpa.…”
Section: Introductionmentioning
confidence: 99%
“…1A), isolated from the fruit of Lindera erythrocarpa that specifically inhibited HCV RNA replication. L. erythrocarpa Makino, belonging to the family Lauraceae, is widely cultured in Asian countries such as Taiwan, Japan, Korea, and China, and its fruits are traditionally used in folk medicine because of their extensive pharmacological properties, such as analgesic, digestive, diuretic, antidotal, and antibacterial properties (15). The lucidone derivatives, such as methyllinderone and methyllucidone, also exhibited anti-inflammation activity and anti-farnesyl protein transferase (16,17).…”
mentioning
confidence: 99%